Analisis Standar Penilaian Pendidikan Di Indonesia ( Komparasi Permendikbud No. 21 Tahun 2022 Dan Permendikbud No. 23 Tahun 2016 ) - Yunianto, Teguh; Rega Pradana, Dhimas (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract This research aims to conduct a comparative analysis between Minister of Education and Culture Regulation (Permendikbud) Number 21 of 2022 and Minister of Education and Culture Regulation Number 23 of 2016 regarding education assessment standards in Indonesia. This type of research is a literature study. Literature study is a series of activities related to methods of collecting library data originating from journals, books and other documents related to theory and information, both past and present, related to the topic under study. The research focus includes the scope of assessment, assessment objectives, assessment procedures, and selection and development of assessment instruments Keywords: Analysis, Assessment standards, Education Indonesia